Teaching broader impacts of science with undergraduate research - Keiler, Kenneth C. (PLoS Biol, 2017)
Science plays an important role in most aspects of society, and scientists face ethical decisions as a routine part of their work, but science education frequently omits or segregates content related to ethics and broader impacts of science. Undergraduate research experiences have the potential to bridge traditional divides in education and provide a holistic view of science. In practice, these experiences can be inconsistent and may not provide the optimal learning environment. We developed a course that combines seminar and independent research elements to support student learning during undergraduate research, makes ethical and societal impacts of science clear by relating them to the students’ own research projects, and develops students’ ethical decision-making skills. Here, we describe the course and provide resources for developing a similar course.